Faktor - Faktor Yang Mempengaruhi Ketepatan Koding Congestive Heart Failure (CHF) Pasien Rawat Inap di RSU Imelda Pekerja Indonesia Medan Tahun 2023 - Hutasoit, Theresia; Sitorus, Mei Sryendang; Simanjuntak, Esraida; Valentina, Valentina (Jurnal Media Informatika, 2024)
Code accuracy is very necessary so that the information generated from diagnoses and medical actions is correct. The accuracy in providing diagnostic codes and medical actions is influenced by coding officers who determine the code based on data in medical records. Coding officers need to attend training related to procedures for determining the right and accurate code. The initial survey at RSU Imelda Pekerja Indonesia Medan found that from 62 medical records of CHF patients in January – March 2023, as many as 29 files (40.3%) did not have the correct diagnosis code. The purpose of this study was to determine the factors that affect the accuracy of coding Congestive Heart Failure (CHF) inpatients at RSU Imelda Pekerja Indonesia Medan. The research method used is descriptive research with a quantitative approach. Data collection by observation method by directly observing what factors affect the accuracy of coding Congestive Heart Failure (CHF) hospitalized patients. The results of the Chi-Square test analysis found that the officer's characteristics affect the accuracy of coding with a P-Value value of 0.011<0.05 for the officer's level of knowledge, a P-Value value of 0.009<0.05 for coding training that has been attended and a P-Value value of 0.000<0.05 for the length of service of the officer. The completeness of the assessment does not affect the accuracy of coding with a P-Value value of >0.05 but the completeness of diagnostic examinations and medical resumes affects the accuracy of coding with a value P-Value 0.002<0.05 and P-Value 0.015<0.05